Are regional and remote Western Australian children eating for good health? An investigation into fruit and vegetable consumption. (19th January 2017) - Godrich, Stephanie L.; Lo, Johnny; Davies, Christina R.; Darby, Jill; Devine, Amanda
Abstract : Issue addressed: Little is known about the fruit and vegetable (F&V) habits of regional and remote Western Australian (WA) children beyond quantities consumed. This study aimed to ascertain the proportion of regional and remote WA children who met the Australian Dietary Guidelines (ADG) for F&V; the types and varieties of F&V consumed; and whether consumption behaviour was associated with remoteness. Methods: Caregiver and child dyads ( n  = 256 dyads) completed similar paper‐based surveys, 196 of these children completed 24‐h dietary records. Statistical analyses were conducted using IBM SPSS (version 23). Results: Overall, children were less likely to adhere to vegetables (15.4%) than fruit (65.8%) guidelines. Adherence to the ADG did not significantly differ between regional and remote locations. However, a higher proportion of remote children consumed dried fruit compared with regional children, while significantly more regional children compared with remote children consumed from the 'pome, tropical and stone fruit' group and the 'starchy vegetables', 'red/orange vegetables' and 'dark green leafy vegetables' groups. Conclusions: Many regional and remote WA children consumed F&V in suboptimal amounts. Further research should aim to ascertain factors that increase or decrease the likelihood of ADG adherence across regional and remote WA and determine why certain F&V variety groups and types differed in consumption across Remoteness Areas. So what: This study provided closer scrutiny of WA children's F&V consumption habits, highlighting the differences in consumption behaviours due to remoteness and identifying specific areas that require further investigation. Abstract : This study used caregiver–child dyads (( n  = 256) and 24‐hour dietary diaries (( n  = 196) to ascertain Australian Dietary Guideline (ADG) adherence among regional/remote Western Australian children. More children met fruit (65.8%) than vegetable (15.4%) recommendations, which were not impacted by remoteness. Fruit and vegetable types and varieties significantly differed between regional/remote locations.